Keteladanan Abraham dalam Teologi Manajemen Pendidikan - Grasela Sinta; Roberth Jekson Msiren; Hurmanisa Hurmanisa; Sarmauli Sarmauli (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study analyzes the exemplary nature of Abraham within the framework of education theological management. Abraham, recognized as the father of faith, embodies values of leadership, wise decision-making, and strong interpersonal relationships with God and others. Utilizing a qualitative approach based on a literature review of various books and scholarly articles, this research aims to explore the managerial principles derived from Abraham’s life and their applicability in contemporary management contexts.